Plasmodium ovale malaria and dengue co-infection in a glucose-6-phosphate dehydrogenase (G6PD) deficiency patient : a case study - Shahimi, Siti Sarah; Aziz, Marniza; Ilham, Nur Ezrin; Awang Hamat, Rukman (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Malaria and dengue are among the most important public health threats in Malaysia. These two-arthropod borne diseases have overlapping mosquito biotopes and clinical manifestations, and co-infections have been associated with increased severity notably on the haematological abnormalities. Dengue caused by four dengue virus (DENV) serotypes has been highly endemic in Malaysia. However, malaria due to Plasmodium ovale (P. ovale) has been rarely reported among Malaysian population. Nonetheless, climate change and increased influx of international travellers and migrants have shifted the parasite boundaries to non-endemic countries. Thus, diagnosis and management of imported malarial infections should rely on the geographical knowledge on the origin of potential Plasmodium species, prompt laboratory testing and public health intervention. Moreover, it would be difficult to clinically differentiate dengue fever (DF) with a potential relapse or partially treated case of P. ovale, and there is absolutely no transmission of this Plasmodium species in our country. Hence, we believed that this case deserved to be reported.